2021
DOI: 10.3390/molecules26082169
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated Diphenyl Ethers and Heavy Metals in a Regulated E-Waste Recycling Site, Eastern China: Implications for Risk Management

Abstract: Serious pollution of multiple chemicals in irregulated e-waste recycling sites (IR-sites) were extensively investigated. However, little is known about the pollution in regulated sites. This study investigated the occurrence of 21 polybrominated diphenyl ethers (PBDEs) and 10 metals in a regulated site, in Eastern China. The concentrations of PBDEs and Cd, Cu, Pb, Sb, and Zn in soils and sediments were 1–4 and 1–3 orders of magnitude lower than those reported in the IR-sites, respectively. However, these were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…19,37 However, the concentrations of these metals in the regulated site in eastern China were generally comparable to those in different urban and industrial areas of China such as Shanghai, Guangdong, Beijing, and Guizhou. 26 It appears that soil in the unregulated e-waste site in Guiyu was the most metal contaminated of all those measured, while newer regulated sites are somewhat elevated in concentrations compared to most reference sites throughout China.…”
Section: ■ Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…19,37 However, the concentrations of these metals in the regulated site in eastern China were generally comparable to those in different urban and industrial areas of China such as Shanghai, Guangdong, Beijing, and Guizhou. 26 It appears that soil in the unregulated e-waste site in Guiyu was the most metal contaminated of all those measured, while newer regulated sites are somewhat elevated in concentrations compared to most reference sites throughout China.…”
Section: ■ Introductionmentioning
confidence: 90%
“…35 In addition, the mean concentrations of cadmium (0.12 μg•g −1 ), copper (27.9 μg•g −1 ), lead (33.4 μg•g −1 ), antimony (2.11 μg•g −1 ), and zinc (54 μg•g −1 ) in soil samples from a regulated site in eastern China were approximately 2 orders of magnitude lower than those (6.82 μg•g −1 for cadmium, 1568 μg•g −1 for copper, 1423 μg•g −1 for lead, 500 μg•g −1 for antimony, and 2978 μg•g −1 for zinc) in an unregulated e-waste recycling site in Guiyu. 26,36 By comparison, the mean concentrations of arsenic (20 μg•g −1 ) and nickel (38.9 μg•g −1 ) in soil samples from the regulated site in eastern China aforementioned were 3.52 and 7.58 times lower than those (70.4 μg•g −1 for arsenic and 295 μg•g −1 for nickel) in an unregulated e-waste recycling site in Guiyu, respectively. 19,37 However, the concentrations of these metals in the regulated site in eastern China were generally comparable to those in different urban and industrial areas of China such as Shanghai, Guangdong, Beijing, and Guizhou.…”
Section: ■ Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It further narrated that the consumption of lettuce and sweet potato caused the most health risk and also revealed that cowpea and cabbage were moderately safe. Another study by Yin et al (2021) revealed that there is a reasonable pollution of PBDEs and heavy metals there in the vegetables in a regulated e-waste recycling site, Eastern China.…”
Section: Heavy Metal Concentration In Relation To Set Threshold and I...mentioning
confidence: 99%
“…For example, printed circuit board scrap is made up of roughly 40% metals, 30% plastics, and 30% ceramics [19]. Some of the substances released from the e-waste are said to be non-hazardous, while others heavy metals such as; antimony (Sb), arsenic (As), bismuth (Bi), cadmium (Cd), cobalt (Co), copper (Cu), indium (In), iron (Fe), lead (Pb), lithium (Li), mercury (Hg), molybdenum (MO), nickel (Ni), palladium (Pd), silver (Ag), tin (Sn), titanium (Ti), and vanadium (V), also many more organic chemicals are considered toxic, nevertheless, based on the amount and the forms of contamination [20][21][22]. Table 2 shows such major types of components of e-waste concerning electrical and electronic equipment.…”
Section: Composition Of E-wastementioning
confidence: 99%